Identification and Assessment of Fluroquinolone Multidrug Efflux Pump in Multidrug Resistant Staphylococcus aureus isolated from Hospital Wastewater in Kuala Lumpur - Mohd Zulkeflle, Siti Norayuni; Mustafa, NurFarahaida; Othman, Nor'azizi; Hara, Hirofumi (International Journal of Integrated Engineering, 2019)
Apart from alterations of target proteins of fluroquinolones, multidrug resistant (MDR) S. aureus can also mediated their resistance via overexpression of efflux pump. However, this mechanism is not well characterized. Absence of known antibiotic resistance genes (ARGs) in the MDR S. aureus isolates have led us to find other mechanism of resistance which could be responsible for their resistance. Therefore, this study was performed to identify the MDR efflux pump genes and evaluate the activity through Ethidium Bromide Cartwheel (EtBrCW) method. The MDR S. aureus were isolated from local hospital wastewater in Kuala Lumpur. 9 of the MDR S. aureus isolates were subjected to PCR for the detection of MDR efflux pump genes. The EtBrCW was used to demonstrate efflux activity as a mechanism of resistance in S. aureus. The result showed only 2 isolates possessed efflux pump genes with low efflux activity. It was observed that many of the isolates did not have conserved MDR efflux pump genes, suggesting there may be other mechanisms of resistance that need further exploration. The fast spreading of these resistance genes could pose serious risk to public health and emergence of superbug which is difficult to treat with available antibiotic